Evaluation of groundwater quality in district Karak Khyber Pakhtunkhwa, Pakistan. Issue 1 (2nd January 2019) - Javed, Tehseen; Sarwar, Tahir; Ullah, Ihsan; Ahmad, Shakeel; Rashid, Sadaf
ABSTRACT: Groundwater is the major source of drinking, domestic, agricultural, and industrial purposes in the arid and semi-arid areas and its quality is important factor determining its suitability. Our objectives were to evaluate the groundwater quality and its suitability for drinking and irrigation, spatial distribution, and homogeneity or heterogeneity levels between the physicochemical parameters. Standards methods were used to analyze the groundwater samples. The result reveals that sodium (Na + ) and chloride (Cl − ) are the most dominant cation and anions. According to hydro-chemical facies, the majority samples water types are Na-Cl, Na-HCO3 − . Wilcox diagram was used to evaluate the groundwater quality, and 60% of samples fall in (C3-S2, C4-S2, and C3-S3) water quality class. Highly significant correlation was observed between Cl − and SO2 4- with Na + and positive correlation between the pH and CO 2 3 − . The cluster analyses indicate that Cl − very close similarities with TDS. The 84% of groundwater samples are unsuitable for the potable use as per WHO guidelines. The findings of this study are playing a crucial role in groundwater management.